Pengaruh Persepsi Kebermanfataan, Kemudahan Penggunaan, Risiko dan Pengetahuan Nasabah Terhadap Penggunaan E-Banking Pada UMKM Di Kabupaten Buleleng - Ningsih, Ni Komang Arya; Diatmika, I Putu Gede (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
E-banking is an example of banking information technology that can provide various benefits for MSME players. But in fact the use of E-banking by UMKMs players is still low. This study aims to determine the effect of perceived usefulness, perceived ease of use, risk perception and customer knowledge on the use of E-banking at UMKMs in Buleleng Regency. This research uses quantitative methods using primary data types. The sample collection method used is probability sampling method, which is done by using stratified random sampling technique. The number of samples obtained using the Solvin formula is 100 people. Analysis of the data used in this study, namely: descriptive statistical analysis, research instrument test, classical assumption test, and hypothesis testing. The results of this study indicate that: 1) perceived usefulness has a significant positive effect on the use of E-banking, 2) perceived ease of use has a significant positive effect on the use of E-banking, 3) perceived risk has a significant negative effect on the use of E-banking, and 4) knowledge customers have a significant positive effect on the use of E-banking.